Future perspectives of the communication and information sector in Ecuador - Yagual Velastegui, Alfredo Marcel; Freire Benítez, María Belén; Orbe Terán, Jonathan Wladimir; Baño Lucio, Luis Alfonso (Revista Universidad de Guayaquil, 2019)
This research aims to determine the economic growth of the Communication and GDP information sector in real terms in Ecuador. For its theoretical support, the theories of the Input-Output model were used. A comprehensive correlational research methodology was applied. In short, running linear regression, correlations, and a nonparametric test like Shapiro-Wilk. As a result, the correlation between the variables was approximately 99% of association, a high level of significance. It is concluded that the communication and information industry have a positive impact on the Gross Domestic Product, real GDP (constant) in Ecuador during the 2007-2017 period.
Keywords: Economic growth; Communication and Information; Input-output model I-O; Ecuador